The mechanism of body–mind integration in the formation of destination attachment: A comparison of first-time and repeat tourists - Dong, Yinyin; Qu, Ying (Frontiers in Psychology, 2022)
By constructing a person-body–mind-place framework of destination attachment, this study explores the physical and mental formation mechanism of destination attachment and examines its dynamics between first-time and repeat tourists. The present study found that multisensory impressions can, directly and indirectly, affect destination attachment through emotional and cognitive psychological mediation. There are differences between first-time tourists and repeat tourists in terms of this mediation path. As the frequency of travel increases, the influence of multisensory impressions gradually increases. The formation of destination attachment is dominated by emotion for first-time tourists, whereas it is dominated by cognition for repeat tourists. Based on these findings, theoretical and practical implications are presented.